Quantification of the horizontal transmission of Mycoplasma synoviae in non-vaccinated and MS-H-vaccinated layers. Issue 4 (4th July 2017) - Feberwee, A.; Dijkman, R.; Klinkenberg, D.; Landman, W. J. M.
ABSTRACT: The number of newly infected birds attributable to one infectious bird per day (= transmission rate β ) was assessed in non-vaccinated and MS-H-vaccinated experimental specified pathogen-free White Leghorns after Mycoplasma synoviae challenge. Furthermore, the effect of vaccination on the shedding of the challenge strain was determined. The following groups were made: a negative control group ( n = 5), a vaccinated (MS-H vaccine by eye drop (>10 5.7 colour changing units/bird)) non-challenged group ( n = 5), two non-vaccinated challenged groups ( n = 18 each) and two vaccinated challenged groups ( n = 18 each). In the challenged groups, six seeder birds were intratracheally inoculated with 10 5.4 colony forming units (CFUs)/bird. Trachea swabs were taken at day (D)2, D3, D4, D5, D7, D9, D11, D14, D17, D21, D25, D28, D32, D35, D42 and D46 after contact with seeders and analyzed with a quantitative PCR able to detect the vaccine and field strain separately. The transmission rate and shedding were estimated using the susceptible exposed infectious transmission model and a linear mixed model, respectively. The mean shedding of the challenge strain was 10 6.4 CFU equivalents M. synoviae /g trachea mucus in vaccinates shedding MS-H, while in the birds not shedding the vaccine (non-vaccinates and vaccinates not shedding MS-H) it was 10 6.9 CFU equivalents M. synoviae /g trachea mucus. In vaccinates shedding MS-H, β was 0.0012 (95% C.I.: 0.00048 – 0.0024), while in birds not shedding vaccine (non-vaccinates and vaccinates not shedding MS-H) a significantly higher β of 0.022 (95% C.I.: 0.015 – 0.031) was found.